2018
DOI: 10.1371/journal.pone.0203441
|View full text |Cite
|
Sign up to set email alerts
|

An integration of phenotypic and transcriptomic data analysis reveals yield-related hub genes in Jatropha curcas inflorescence

Abstract: Jatropha curcas is an oil-rich seed crop with huge potentials for bioenergy production. The inflorescence carries a number of processes that are likely to affect the overall yield potentials; floral development, male-to-female flower ratio, floral abscission and fruit set. In this study, a weighted gene co-expression network analysis which integrates the transcriptome, physical and simple sugar data of J. curcas inflorescence was performed and nine modules were identified by means of hierarchical clustering. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
(87 reference statements)
0
1
1
Order By: Relevance
“…The low yield of J. curcas plants reported in some studies (Matos et al, 2012;Govender et al, 2018;Lama et al, 2018) was not found in the present study. Plants treated with trinexapac-ethyl + prohexadione-Ca (T3) produced, on average, 1.306 kg per plant, and control plants produced 0.927 kg per plant.…”
Section: Resultscontrasting
confidence: 87%
“…The low yield of J. curcas plants reported in some studies (Matos et al, 2012;Govender et al, 2018;Lama et al, 2018) was not found in the present study. Plants treated with trinexapac-ethyl + prohexadione-Ca (T3) produced, on average, 1.306 kg per plant, and control plants produced 0.927 kg per plant.…”
Section: Resultscontrasting
confidence: 87%
“…Protein TEA021735.1 has 1,361 interactions found in Module_1 that has important role in protein kinase activity and might be involved in regulatory processes in reproduction through glucose signalling [41]. Protein TEA006404.1 having KO id K13998 was found to have 728 interactions, and may have an important role in nucleotide metabolism in response to drought and heat stresses [42].…”
Section: Resultsmentioning
confidence: 99%